Pengaruh Kuliah Konseptualisasi dengan Peta Konsep pada Awal Pelatihan Keterampilan Medik terhadap Nilai OSCE Akhir Blok - B P Suryosubianto; Yayi Suryo Prabandari; Ova Emilia (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2013)
Background: OSCE is known as a skills examination method with high level of objectivity and reliability. Many efforts explore to increase OSCE achievement. Increasing the underlying knowledge of medical skills prior to a skills training proven to improve the skills achievement. A lecture delivered using concept maps, are considered better than the conventional lecture. The objective of this study is to find out that a lecture using concept maps before splinting skills training will increase the OSCE scores.Method: A quasi-experimental post test only study was conducted among 151 students of the Faculty of Medicine, General Achmad Yani University studying trauma at the fourth semester. The 74 students of the experiment group got a trauma lecture using concept maps, the 77 students of the control group got a trauma lecture without concept maps. The result of the splinting OSCE scores of the two groups were compared and statistically analyzed.Results: The average value of the OSCE score of the experiment group was significantly higher (89.10) than the control group (84.93). There were no differences in OSCE score among different gender, grade point average value, and the expertise of the instructors.Conclusion: Lecture in trauma before splinting skills training using the concept map that explains on the conceptualization (i.e. indication, contraindication, and how to prevent, identify and treat the splinting complications), will increase the score of OSCE. Demonstration of cases according to the theme of the subject involving a group of students, will enhance student understanding of the lecture topics.